„Public sentiment is everything“: Britiske og danske avisers dækning af krigen i Afghanistan og indflydelsen på den offentlige opinion - Høgsbro Larsen, Søren (Politik, 2010)
A majority of respondents in every public survey in Great Britain from 2006 to 2009 has consistently been opposed to the war in Afghanistan, while in Denmark there has been widespread support for the war. In this article, it is analyzed which differences there are between Danish and British newspapers in their coverage of Afghanistan and which significance these differences can have for public opinion on the war. With a theoretical grounding in social constructivism and media theories, a generally applicable analytical framework is developed, integrating the concepts of framing and agenda-setting. Analyzing 221 articles from August 2009, it is concluded that there are major differences between British and Danish coverage, which can have contributed to the differences in public opinion. A greater focus on own casualties and the government’s responsibility is evident in British newspapers. Furthermore, it is concluded that the British coverage to some degree has been institutionalised.